ANALISIS PENGARUH KONSENTRASI RAGI DAN JENIS NUTRISI PADA FERMENTASI MENGGUNAKAN SACCAROMYCES CEREVISEAE TERHADAP PEMBUATAN BIOETANOL DARI LIMBAH KULIT PISANG KEPOK - Aldi Bayu Iskandar (Jurnal Pengabdian Vokasi, 2022)
Analysis of the Effect of Yeast Concentration and Types of Nutrients on Fermentation using Saccharomyces cereviseae on the Production of Bioethanol from Kepok Banana Peel Waste]. Kepok banana peel as one of the household wastes and only to be thrown away us as researchers should be able to utilize banana peel waste to benefit the surrounding community. This banana peel waste should be treated so that it can be useful for the surrounding community, The enzymatic hydrolysis method is more often used because it is more environmentally friendly compared to acid catalysts. This study examines the treatment of NaOH, H2SO4 0.5 n Urea, ZA and NPK. In making bioethanol the substrate in the fermentation concentration starter are 2 and 3% and the study was carried out for 72  and 144 hour at room temperature (25-35oC) significant